Carbon Paste Electrode Modified with PMBP: A Sensitive Sensor for Electrochemical Detection of Acetaminophen - Mohamad Syahrizal Ahmad, Illyas Md Isa, Norhayati Hashim, Mohamad Idris Saidin (Tanjung Malim, 2024)
Carbon Paste Electrode Modified with PMBP: A Sensitive Sensor for Electrochemical Detection of Acetaminophen by Mohamad Syahrizal Ahmad, Illyas Md Isa, Norhayati Hashim, Mohamad Idris Saidin